Another world is possible : Insights from the Oded Grajew, originator of the World Social Forum - Grajew, Oded.; Global academy for Entrepreneurship; Rooy Media; SKOLL Foundation (ASHOKA Innovators for the Public.)
Oded grajew describes the founding of the World Social Forum, a unique transnational process for dialogue.collaboration and coalitio-building.
DVD.
Keywords: Economic development -- Citizen Participation; Globalization -- Social aspects; International economic relations; World Social Forum